2014
DOI: 10.1098/rsta.2013.0299
|View full text |Cite
|
Sign up to set email alerts
|

Towards a shock tube method for the dynamic calibration of pressure sensors

Abstract: In theory, shock tubes provide a pressure change with a very fast rise time and calculable amplitude. This pressure step could provide the basis for the calibration of pressure transducers used in highly dynamic applications. However, conventional metal shock tubes can be expensive, unwieldy and difficult to modify. We describe the development of a 1.4 MPa (maximum pressure) shock tube made from unplasticized polyvinyl chloride pressure tubing which provides a low-cost, light and easily modifiable basis for es… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(53 citation statements)
references
References 8 publications
0
49
0
Order By: Relevance
“…Side-wall mounted sensors provide a means of estimating the shock speed, and therefore the expected pressure step. Experiments were carried out in a prototype shock tube at NPL, to test the applicability of shock tube theory in predicting pressure gain across the reflected shock [24]. This work found good agreement between the changes in pressure predicted by ideal gas theory and the changes in observed sensor output, for a number of different gases, shock wave velocities, and driven section pressure magnitudes.…”
Section: Shock Tube As a Primary Calibration Systemmentioning
confidence: 90%
See 1 more Smart Citation
“…Side-wall mounted sensors provide a means of estimating the shock speed, and therefore the expected pressure step. Experiments were carried out in a prototype shock tube at NPL, to test the applicability of shock tube theory in predicting pressure gain across the reflected shock [24]. This work found good agreement between the changes in pressure predicted by ideal gas theory and the changes in observed sensor output, for a number of different gases, shock wave velocities, and driven section pressure magnitudes.…”
Section: Shock Tube As a Primary Calibration Systemmentioning
confidence: 90%
“…For example, in [27] it was found that for relatively weak shocks, post-shock oscillations were not eliminated by increasing the tube length (though amplitude of the oscillations could be substantially reduced). Experimental investigations into the effects of non-ideal diaphragm burst were made in the prototype shock tube at NPL [24]. Repeated firings were made with diaphragms of different material; aluminium, brass of varying thickness, and copper.…”
Section: Shock Tube As a Primary Calibration Systemmentioning
confidence: 99%
“…[39] Non-uniform rupture of the shock-generating membrane may also occur, affecting the shock wave-front. [11] These and other non-ideal effects will produce pressure and temperature changes that differ from theory. It is important to remember that the shock tube is not the pressure standard (we are not relying on shock tube theory to determine the pressure); we are relying on it only to provide a reproducible and characteristic time-varying pressure that can be interrogated by the spectroscopic system.…”
Section: 1 Methodsmentioning
confidence: 99%
“…Modern approaches taken to develop the needed standards use modeling of dynamic systems (sensors) or modeling of pressure sources (shock tubes) which are difficult to verify without independent standards or measurements. [11, 13] We propose a fundamentally different method that relies on measuring the quantum mechanical properties of molecules to determine pressure and temperature. Our proposed technique will utilize line-of-site absorption spectroscopy to measure time-varying pressure and temperature in a gas of known concentration, using the unique quantum mechanical characteristics of the molecules as the standard for pressure.…”
Section: 1 Conclusionmentioning
confidence: 99%
See 1 more Smart Citation